Silymarin and Vanillic Acid Silver Nanoparticles Alleviate the Carbon Tetrachloride-Induced Nephrotoxicity in Male Rats. (2nd February 2023) - El Rabey, Haddad A.; Alamri, Eman S.; Alzahrani, Othman R.; Salah, Nouran M.; Attia, Eman S.; Rezk, Samar M.
Abstract : Natural copolymer (e.g., chitosan-loaded) and synthetic (e.g., silver nitrate-loaded) nanopolymers have many medical applications in drug delivery research for enhancing the effectuality of traditional medicine. This study aimed to investigate the potential protective activity of vanillic acid, silver nanoparticles (AgNPs) of vanillic acid, and silymarin against carbon tetrachloride (CCl4 )-induced nephrotoxicity in male rats. Rats were divided into five groups; the first group (G1) was a negative control, and the other rats were treated intraperitoneally with CCl4 to induce kidney toxicity twice weekly, and then divided into four groups, G2 was a positive control and left without treatment, the third group was treated with vanillic acid, the fourth (G4) was treated with vanillic acid-AgNPs, and the fifth (G5) was treated with silymarin. In G2, renal function indices (urea, creatinine, and uric acid) showed elevated levels indicating renal toxicity. Na, K, and Ca ions were decreased, whereas Cl − was increased. Antioxidants (glutathione S-transferase, glutathione reduced, total antioxidant capacity, superoxide dismutase, and catalase) were decreased, whereas lipid peroxidation was increased in the kidney tissue homogenate. IL1 was increased, whereas CYP-450 was decreased. In the treated group, all biochemical and renal tissue texture were alleviated as a result of treatment with vanillic acid in G3, vanillic acid AgNPs in G4, and silymarin in G5. Vanillic acid AgNPs and silymarin treatment in G4 and G5, respectively, were more efficient than vanillic acid in G5 in protecting the kidneys against CCl4 -induced nephrotoxicity.